Bir Kimlik Tespiti, Kolektif Şuur ve Sosyal Bir Travma Olarak Hocalı Faciası - Garagözov, Rauf (Fırat University, 2013)
Karabağ çatışmalarında insanların yaşadığı çok sayıdaki facia ve acımasız şiddet dolu sahneler arasında 1992 yılı Şubat ayının 25’inden 26’sına geçen gece yaşanmış olaylar kendine has amansızlığıyla ayrılır. Bu gecede Ermeni militanları, BDT’ye bağlı Birleşik Silahlı Kuvvetlerinin 366. Alayına mensub askerlerin desteğiyle, sadece birkaç saat içinde Azerbaycan’ın Hocalı şehrini yeryüzünden silerek yüzlerce sivil insanı işkenceyle öldürüldü.1 Hocalı faciasının, şüphesizdir ki hukuki, siyasi, iktisadi, sosyal vb. çeşitli yönleri bulunmaktadır. Burada facianın bazı psikolojik yönleri ele alınacaktır.

The article considers some socio-psychological and socio-cultural aspects of the Khojaly tragedy. In particular the author analyses that event within the framework of such notions as a collective trauma and collective memory, and discuses the various ways in which Azerbaijani society could relate to the trauma. It is argued that this event was not only a psychic trauma for those who were the participants or victims of massacre but a collective trauma for the entire population, because people felt a threat to their collective identity. Looking into different ways of dealing with collective trauma the author suggests such method as “working through it” which requires broad and all-sided discussion of the traumatic event, in order to make sense of their causes, factors, and consequences and the definition of moral and legal responsibility for what took place. The author especially points out the role of international organizations in bringing justice and punishment of criminals irrespective of any geopolitical and economic calculations
The Khojaly Tragedy as A Collective Trauma and Factor of Collective Memory and Identity